Examining the Effect of Consuming C8 Medium-Chain Triglyceride Oil for 14 Days on Markers of NLRP3 Activation in Healthy Humans - Helena Neudorf; Garett Jackson; Jonathan P. Little (Journal of Nutrition and Metabolism)
Chronic, low-grade inflammation is associated with the development of numerous diseases and is mediated in part by overactivation of the NLRP3 inflammasome. The ketone body beta-hydroxybutyrate (βHB) suppresses the NLRP3 inflammasome and alters intracellular signalling pathways in vitro and in animal models; however, this effect has not yet been shown in vivo in humans. The purpose of this single-arm pilot trial was to determine if consuming 15 mL of C8 medium-chain triglyceride (trioctanoin; MCT) oil, which induces mild elevation of βHB, twice daily (30 mL total) for 14 days would suppress markers of NLRP3 inflammasome activation in young, healthy humans while following their habitual diet. Consuming a single dose of 15 mL of C8 MCT oil significantly raised blood βHB from fasting at 60 minutes and 120 minutes post ingestion (both P<0.05). However, consumption of C8 MCT oil for 14 days did not impact markers of monocyte NLRP3 inflammasome activation compared to baseline. Specifically, caspase-1 activation and secretion of its downstream product interleukin (IL)-1β were unchanged following 14 days of C8 MCT oil supplementation when measured in unstimulated and LPS-stimulated whole blood cultures (all P>0.05). Acetylation of histone H3 on the lysine residue 9 was unchanged (P<0.05) and acetylation of lysine residue 14 was decreased (P<0.05) following 14 days of supplementation. Thus, adding twice daily C8 MCT oil supplementation to the habitual diet of young, healthy humans does not appear to suppress NLRP3 inflammasome activation.